Esoterisme Tafsior dalam Pemahaman Al-Qur'an - Rifai, Ahmad (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2024)
This article presents an esoteric interpretation of the understanding of the Qur'an by the Sufis as a result of the internalization of Qur'anic values and prophetic traditions that are always seen in a world of ambiguity. Namely exoteric meaning and esoteric meaning. This study strengthens the opinion that the interpretation of the Qur'an carried out by Sufis has a scientific basis of takwili that is sourced and does not conflict with the Qur'an. This article expresses the disapproval of the Sufis on the circulation of statements by philosophers, theologians or mutakallimun and also legal experts (fuqaha') who often negate the esoteric dimension in understanding the Qur'an. Through esoteric interpretation of the understanding of the Qur'an, it has placed the Qur'an as a hammalat lil wujuh, which can accommodate various meanings, so that new meanings are very likely to be accommodated by it without experiencing difficulties and obstacles.